Double imposition of “VAT” in importation and utilizing of services: ¿problem of interpretation or regulation? - Assereto Bossio, Juan José (2016)
This article addresses the discussion about the validity in the interpretation of the double impact of “VAT” on a single economic event by setting two different taxable events. Likewise, it is explained if this interpretation infringed the systematic of tax and violates constitutional principles taxation such as equality and non-confiscatory.